The living cosmos our search for life in the universe - Impey, Chris (Cambridge University Press, 2011)
Astrobiology, the study of life in space, is one of today's fastest growing fields of science. In this accessible and elegantly reasoned book, scholar and researcher Impey explores the foundations of this rapidly developing discipline, where it's going, and what it's likely to find. If Earth is not the only planet, it is so far the only living one that we know of. Impey reveals the incredible proliferation and variety of life on Earth, paying special tribute to some of its hardiest life forms, extremophiles, a dizzying array of microscopic organisms that can survive extreme heat and cold, live deep within rocks, or thrive in pure acid. From there, Impey investigates the potential for life beyond our own world, providing portraits of the individuals who have devoted their lives to the search.--From publisher description.